PERKEMBANGAN TEORI SELF-TALK DALAM PENDEKATAN RATIONAL EMOTIVE BEHAVIORAL THERAPY DALAM PERSPEKTIF ISLAM - Ika Aulia; N Nurjannah (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2023)
The Self Talk technique is one of the modern methods and is based on a method of approaching reason and mind without considering the heart/qolbu. Even though it is better to use your conscience and heart as a servant of God to hold the voice of conscience, which always leads to goodness. Therefore, this study aims to find out how the Self Talk technique develops through the synchronization of thoughts and conscience, or qolbu. Literature analysis based on various journal articles, books, and papers is the research methodology used. One of the modern strategies is the self-talk method. This essay discusses the development of the Self Talk technique, understanding and use of the technique, its advantages and disadvantages, as well as the author's criticism of the approach. It is known from the findings and debates that this Self Talk approach can be developed by aligning the mind and heart. The existence of this harmony is very beneficial for understanding human nature and attaining true pleasure.Keywords: Self Talk Techniques, Qolbu, Islamic Views